Reasons for Choice of Antibiotic for the Empirical Treatment of CAP by Canadian Infectious Disease Physicians - Jacob Pendergrast; Thomas Marrie (Canadian Journal of Infectious Diseases)
BACKGROUND: Previous studies have documented substantial variation in physician prescribing practices for the treatment of community-acquired pneumonia. Much of this variation is the result of empirical treatment, in which physicians must choose antibiotics in the a8bsence of culture and sensitivity data.